Impact of the COVID-19 outbreak on out-of-hospital cardiac arrest management and outcomes in a low-resource emergency medical service system: a perspective from Thailand - Riyapan S. (2023)
Background: The impact of the coronavirus disease 2019 (COVID-19) outbreak on out-of-hospital cardiac arrest (OHCA) has been of interest worldwide. However, evidence from low-resource emergency medical service systems is limited. This study investigated the effects of the COVID-19 outbreak on the prehospital management and outcomes of OHCA in Thailand. Methods: This multicentered, retrospective, observational study compared the management and outcomes of OHCA for 2 periods: pre-COVID-19 (January–September 2019) and during the outbreak (January–September 2020). Study data were obtained from the Thai OHCA Network Registry. The primary outcome was survival rate to hospital discharge. Data of other OHCA outcomes and prehospital care during the two periods were also compared. Results: The study enrolled 691 patients: 341 (49.3%) in the pre-COVID-19 period and 350 (50.7%) in the COVID-19 period. There was a significant decrease in the survival rate to discharge during the COVID-19 outbreak (7.7% vs 2.2%; adjusted odds ratio [aOR], 0.34; 95% confidence interval [CI], 0.15–0.95). However, there were no significant differences between the 2 groups in terms of their rates of sustained return of spontaneous circulation (33.0% vs 31.3%; aOR, 1.01; 95% CI, 0.68–1.49) or their survival to intensive care unit/ward admission (27.8% vs 19.8%; aOR, 0.78; 95% CI, 0.49–1.15). The first-responder response interval was significantly longer during the COVID-19 outbreak (median [interquartile range] 5.3 [3.2–9.3] min vs 10 [6–14] min; P < 0.001). There were also significant decreases in prehospital intubation (66.7% vs 48.2%; P < 0.001) and prehospital drug administration (79.5% vs 70.6%; P = 0.024) during the COVID-19 outbreak. Conclusion: There was a significant decrease in the rate of survival to hospital discharge of patients with OHCA during the COVID-19 outbreak in Thailand. Maintaining the first responder response quality and encouraging prehospital advanced airway insertion might improve the survival rate during the COVID-19 outbreak.